Organic Matter Preservation and Incipient Mineralization of Microtubules in 120 Ma Basaltic Glass - Izawa, Matthew R. M.; Dynes, James J.; Banerjee, Neil R.; Flemming, Roberta L.; MacLean, Lachlan C. W.; Hetherington, Callum J.; Matveev, Sergei; Southam, Gordon (Frontiers in Earth Science, 2019)
Hollow tubular structures in subaqueously-emplaced basaltic glass may represent trace fossils caused by microbially-mediated glass dissolution. Mineralized structures of similar morphology and spatial distribution in ancient, metamorphosed basaltic rocks have widely been interpreted as ichnofossils, possibly dating to ~3.5 Ga or greater. Doubts have been raised, however, regarding the biogenicity of the original hollow tubules and granules in basaltic glass. In particular, although elevated levels of biologically-important elements such as C, S, N and P as well as organic compounds have been detected in association with these structures, a direct detection of unambiguously biogenic organic molecules has not been accomplished. In this study, we describe the direct detection of proteins associated with tubular textures in basaltic glass using synchrotron X-ray spectromicroscopy. Protein-rich organic matter is shown to be associated with the margins of hollow and partly-mineralized tubules. Furthermore, a variety of tubule-infilling secondary minerals, including Ti-rich oxide phases, were observed filling and preserving the microtextures, demonstrating a mechanism whereby cellular materials may be preserved through geologic time.